A Study of Acute Poisoning Cases Admitted to the University Hospital Emergency Department in Tabriz, Iran - Oraie, Mehdi; Hosseini, Mir-Jamal; Islambulchilar, Mina; Hosseini, Seyed-Hasan; Ahadi-Barzoki, Mehdi; Sadr, Habib; Yaghoubi, Hashem (Drug Research, 2017)
Chemical substances have an important threat due to extensive use in medicine, agriculture, industry and environment. In this retrospective study, etiological and demographic characteristics of acute poisoning cases admitted to a hospital in Iran were investigated. We compared these data with those reported from other parts of the country and the international experiences to evaluate any difference if exists. 7 052 poisoned cases admitted to the hospital from April 2006 to March 2013, by data collected from the medical record in poison center section. According to our results there is a predominance of male patients and the majority of the poisoned patients were between 20–30 years old. Drug poisoning was the most common cause of poisonings. The most frequently involved drugs were benzodiazepines and antidepressants. The seasonal distribution of our study showed a peak in summer. To prevent acute poisonings, the social education about the risk assessment of central nervous system-acting drugs and reduction of the exposure period of people to pesticides are recommended. This study suggested a proper educational program for the public and primary care units. Our results provide useful information for preventive strategies.
Keywords: acute poisoning; medical record; suicide; prevention strategy; Iran; Tabriz; epidemiology